Appendix to The Effect of Work Environments on Productivity - Zimmermann, Thomas; Johnson, Brittany; Bird, Christian; Zimmermann, Tom (Microsoft Research, 2015)
This reports contains supplemental information: (1) the text of the recruitment survey, (2) the guide for the semi-structured interviews, and (3) the text of the follow-up survey.